Quality of Life and Functional Outcomes after Multiligament Knee Reconstruction - Hatch, George F. Rick, III; Villacis, Diego; Damodar, Dhanur; Dacey, Michael; Yi, Anthony (The Journal of Knee Surgery, 2018)
We aimed to determine factors that affect the quality of life of patients undergoing a standardized surgical and postoperative management protocol for knee dislocations. A total of 31 patients (33 knees) were included in this study. We contacted patients at a minimum of 12 months postoperatively (mean: 38 months; range, 12–111 months) and administered the previously validated Multiligament Quality of Life questionnaire (ML-QOL), 2000 International Knee Documentation Committee Subjective Knee Form (IKDC), and Lysholm Knee Scoring Scale. We performed independent two-sample t-tests and age-adjusted multivariable linear regression analysis to examine the difference in these scores. Patients who underwent previous knee ligament surgery had significantly worse mean ML-QOL scores relative to patients who did not undergo previous knee ligament surgery (114.3 versus 80.4; p = 0.004) (higher score indicates worse quality of life). All other differences in the ML-QOL scores were not statistically significant. IKDC and Lysholm scores did not differ significantly with regards to the studied variables. Among patients with no previous knee ligament surgery, patients undergoing surgery within 3 weeks of injury had significantly worse mean ML-QOL scores relative to patients undergoing surgery greater than 3 weeks after their injury (98.7 versus 74.7; p = 0.042) and patients with Schenck classification of III or IV had significantly worse mean ML-QOL scores relative to patient with a Schenck classification of I or II (88.7 versus 62.9; p = 0.015). We found that patients with a previous history of knee ligament surgery had a significantly worse quality of life relative to those with no history of knee ligament surgery. This is a level III, retrospective cohort study.
Keywords: multiligament knee injury; knee dislocation; quality of life; functional outcomes